Loss of Discoidin Domain Receptor 1 Predisposes Mice to Periodontal Breakdown. (December 2019) - Chavez, M.B.; Kolli, T.N.; Tan, M.H.; Zachariadou, C.; Wang, C.; Embree, M.C.; Lira Dos Santos, E.J.; Nociti, F.H.; Wang, Y.; Tatakis, D.N.; Agarwal, G.; Foster, B.L.
The discoidin domain receptors, DDR1 and DDR2, are nonintegrin collagen receptors and tyrosine kinases. DDRs regulate cell functions, and their extracellular domains affect collagen fibrillogenesis and mineralization. Based on the collagenous nature of dentoalveolar tissues, we hypothesized that DDR1 plays an important role in dentoalveolar development and function. Radiography, micro–computed tomography (micro-CT), histology, histomorphometry, in situ hybridization (ISH), immunohistochemistry (IHC), and transmission electron microscopy (TEM) were used to analyze Ddr1 knockout ( Ddr1 −/− ) mice and wild-type (WT) controls at 1, 2, and 9 mo, and ISH and quantitative polymerase chain reaction (qPCR) were employed to assess Ddr1 / DDR1 messenger RNA expression in mouse and human tissues. Radiographic images showed normal molars but abnormal mandibular condyles, as well as alveolar bone loss in Ddr1 −/− mice versus WT controls at 9 mo. Histological, histomorphometric, micro-CT, and TEM analyses indicated no differences in enamel or dentin Ddr1 −/− versus WT molars. Total volumes (TVs) and bone volumes (BVs) of subchondral and ramus bone of Ddr1 −/− versus WT condyles were increased and bone volume fraction (BV/TV) was reduced at 1 and 9 mo. There were no differences in alveolar bone volume at 1 mo, but at 9 mo, severe periodontal defects and significant alveolar bone loss (14%; P  < 0.0001) were evident in Ddr1 −/− versus WT mandibles. Histology, ISH, and IHC revealed disrupted junctional epithelium, connective tissue destruction, bacterial invasion, increased neutrophil infiltration, upregulation of cytokines including macrophage colony-stimulating factor, and 3-fold increased osteoclast numbers ( P  < 0.05) in Ddr1 −/− versus WT periodontia at 9 mo. In normal mouse tissues, ISH and qPCR revealed Ddr1 expression in basal cell layers of the oral epithelia and in immune cells. We confirmed a similar expression pattern in human oral epithelium by ISH and qPCR. We propose that DDR1 plays an important role in periodontal homeostasis and that absence of DDR1 predisposes mice to periodontal breakdown.